Relation between the composition and properties of carbon nanotubes paste electrodes (CNTPEs) - Mikysek, Tomáš; Stočes, Matěj; Švancara, Ivan; Ludvík, Jiří (Univerzita Pardubice, 2010)
Two types of carbon pastes were prepared, examined and characterized. Particular attention has been paid to the changes of the ohmic resistance, relative to the dependence on the composition of a carbon nanotubes paste electrode (CNTPE) and the respective constituents used. The results were compared with those of "classic" carbon paste electrode (CPE) based on graphite powder and the differences in physical as well as electrochemical properties were discussed and explained. As found, the most evident difference was in the optimal (applicable, employable) carbon-to-binder ratio of the paste. Whereas the CPE could be used only up to 20% (m/m) of the oil, the CNTPE allowed us to go up to 60% (m/m) of the same binding liquid. Finally, some problems connected with homogeneity and stability of carbon paste mixtures as such are also discussed.
Keywords: carbon nanotube paste electrode; carbon paste electrode; characterisation; cyclic voltammetry; resistance measurements